Information Technology Risk Control of University in a Work from Home Situations - Iqbal Santosa; Rahmat Mulyana (Journal of Information System and Informatics, 2022)
The University is one of the educational institutions affected by the COVID-19 pandemic. Most of its activities, which are academic management, human resource management, information technology services, and so on were changed into WFH (Work from Home) supported by information technology. Utilization of information technology in supporting WFH can create various risks and needs to be controlled either preventive, detective, or corrective to minimize the impact. This research will focus on planning for university information technology risk control in working from home conditions by referring to the ISO 31000:2018 standard for risk management processes, COBIT 5 Generic Risk Scenario for defining risk scenarios, and DoD Instruction 8500.2 and NIST SP 800-53 in the identification of risk controls. The resulting solution is in the form of a risk treatment plan. This solution is expected to assist universities in identifying risks related to information technology and planning controls related to the implementation of work-from-home in their environment.